The Emperors new groove - Dindal, Mark.; Fullmer, Randy; Spade, David; Goodman, John, 1952-; Kitt, Eartha; Warburton, Patrick; Malick, Wendie; Sting (Musician); Hartley, David, composer; Debney, John.; Walt Disney Pictures; Walt Disney Home Entertainment (Firm); et al. ([United States] : Walt Disney Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2005)
The emperor is turned into a llama by his ex-administrator and must regain his throne with the help of a llama herder. Includes never-before-seen footage and a sneek peak at Kronk's New Groove.
English or French language track; closed captioned.
DVD; region 1; widescreen 1.66:1, enhanced for 16x9 televisions; DTS 5.1 digital surround, Dolby Digital 5.1 surround sound.
Voices, David Spade, John Goodman, Eartha Kitt, Patrick Warburton, Wendie Malick.
Lyrics by Sting; music by Sting and David Hartley; score composed and conducted by John Debney; art director, Colin Stimpson; editor, Pamela Ziegenhagen-Shefland.
Originally produced as a motion picture in 2000.
MPAA rating: G.
Keywords: Emperors -- Juvenile drama; Llamas -- Juvenile drama; Kings, queens, rulers, etc. -- Drama; Llamas -- Drama; Emperors -- Juvenile drama; Feature films; Children's films; Animated films; Video recordings for the hearing impaired